Atomic layer superconductivity. (8th May 2014) - Stępniak, Agnieszka; Leon Vanegas, Augusto; Caminale, Michael; Oka, Hirofumi; Sander, Dirk; Kirschner, Jürgen; Yurimoto, Hisayoshi
<x xml:space="preserve">Abstract</x> We present scanning tunneling microscopy (STM) studies of superconductivity of single layer Pb and Pb islands on Si(111). We perform temperature‐dependent measurements of the differential conductance from 0.38 to 4 K in fields of up to 6 T to extract the critical temperature TC for the onset of superconductivity. We find TC = 1.5 K for a single layer Pb on Si(111), and a critical out‐of‐plane field of 150 mT. This deviates from bulk Pb, where TC = 7.2 K and HC = 80 mT are reported. Our results provide the temperature dependence of the superconducting gap 2 Δ. A description of this dependence in the framework of the Bardeen–Cooper–Schrieffer theory indicates an energy gap of 2 Δ0 = 0.7 meV, considerably less than the 2.7 meV found for bulk Pb. We observe that the insertion of a single layer Ag between Pb and Si suppresses superconductivity in the Pb film even at the lowest temperature of 0.38 K. Pb islands on Ag/Si(111) exhibit superconductivity. Our position‐dependent STM studies from a nine‐layer tall Pb island into the surrounding non‐superconducting Pb wetting layer on Ag/Si(111) reveal an extension of a superconducting gap in spectroscopy up to 20 nm away from the Pb island edge at 0.38 K. © 2014 The Authors Surface and Interface Analysis Published by John Wiley & Sons Ltd.